Using dynamic geometry software to examine its effects on student progression through the van Hiele levels - Lehman, Andrew (My University, 2024)
Geometry is a strand of mathematics that can benefit individuals in many areas of life. Test results, such as the TIMSS results, indicate that geometry is an area for growth among American students. With a need for students to better understand geometry, several academic standards have been created to direct geometry instruction in the United States. Aside from this growing need, advances in technology have been introduced to classrooms. Dynamic geometry software, such as GeoGebra, is an example of this technology. Does GeoGebra help students develop their geometric reasoning skills? This study used a mixed methods design to investigate the effects that GeoGebra has in the progression of fifth-grade students through the first three levels of the van Hiele theory.
Keywords: van Hiele levels; Geometry; Dynamic geometry software